Factors Predicting Insecticide-Treated Bednet Use among Children under Age Five in Female-Headed Households in Ghana: An Analysis of the 2019 Malaria Indicator Survey - Desmond Klu; Grace Frempong Afrifa-Anane; Michael Larbi Odame (Advances in Public Health)
Background. Malaria remains a major cause of death for children under five in most sub-Saharan African countries. Previous research has indicated a potential role of the sex of household heads in household health-seeking behaviour. However, there is limited knowledge on the factors that affect the use of insecticide-treated bednets among children under five residing in female-headed households (FHHs) in Ghana. This paper aims to examine the household factors that influence insecticide-treated bednet (ITN) use among children under five living in FHH in Ghana. Methods. The study used data from the 2019 Ghana Malaria Indicator Survey (GMIS), which included a weighted sample of 2,018 female household heads across the 16 regions of Ghana. This survey was carried out between September 25 and November 24, 2019. Data analysis was performed using SPSS version 25, employing both descriptive and binary logistic regression modelling. A P value of less than 0.05 was considered statistically significant. Results. Only 18% of children under five living in FHHs slept under ITNs. Children under age five residing in female headed household with poorest (aOR = 2.54; CI: 1.19–5.39), poorer (aOR = 2.65; CI: 1.42–4.93), and middle (aOR = 1.97; CI: 1.13–3.44) wealth index and with 5–10 (aOR = 4.09; CI: 3.02–5.54) and 11+ (aOR = 8.56; CI: 2.90–25.28) household members were more likely to use ITN for malaria prevention. However, children living with older female household heads aged 70 years and above (aOR = 0.12; CI: 0.07–0.21), 60–69 years (aOR = 0.23; CI: 0.14–0.38), and those residing in urban areas (aOR = 0.59; CI: 0.43–0.82) were less probable to sleep under treated bednet. Conclusion. The study recommends continuous and intensified advocacy campaigns in ITN use among poor households headed by females and urge the relevant stakeholders to target older FHHs for support that would encourage the use of ITNs among children.